Challenges for Relative Effectiveness Assessment and Early Access of Cancer Immunotherapies in Europe - Pavlovic, Mira (Frontiers in Medicine, 2016)
Clinical endpoints relevant for relative effectiveness assessment (REA) reflect how patients feel, function, or survive. Outcome data requested by Health Technology Assessment (HTA) bodies in Europe to support reimbursement of an anticancer drug are based on final endpoints coming from completed comparative phase 3 trials; overall survival improvement is the preferred criterion for the demonstration of the patient benefit in this field. Recent arrival of new treatments that target identified functional genetic mutations (“targeted therapies”) or PD-1/PD-L1,2 axis (“immunotherapies”) and their combinations have profoundly changed treatment strategies in cancers as they considerably improve patient survival, but also raise new challenges in REA and decision making process in Europe as compared to the REA of “classical” chemotherapies. In addition, recent regulatory initiatives to support accelerated clinical development and approval of innovative cancer immunotherapies based on non-final endpoints, such as Priority Medicines (PRIME) through the European Medicines Agency (EMA), represent an additional challenge for HTA bodies and decision makers. In order to support adequate data generation for REA of anticancer drugs and especially for drugs candidates for accelerated assessment and early access to market, a close and open dialogue of all stakeholders involved in development of such drugs is crucial